Octodon degus laboratory colony management principles and methods for behavioral analysis for Alzheimer’s disease neuroscience research - B. Maximiliano Garduño; Todd C. Holmes; Todd C. Holmes; Robert M. J. Deacon; Xiangmin Xu; Xiangmin Xu; Xiangmin Xu; Patricia Cogram; Patricia Cogram (Frontiers in Aging Neuroscience)
The Chilean degu (Octodon degus) is a medium sized, long-lived rodent with traits that make them a natural model for neuroscience research. Their social behaviors, diurnality, and extended developmental time course, when compared to other rodents, make them useful for social behavioral, chronobiology, and developmental research. Lab-kept degus have a long lifespan (5–8 years) and may naturally develop age-related diseases that resemble Alzheimer’s disease. While there is significant interest in using the Octodon degus for neuroscience research, including aging and Alzheimer’s disease studies, laboratory management and methods for degus research are currently not standardized. This lack of standardization potentially impacts study reproducibility and makes it difficult to compare results between different laboratories. Degus require species-specific housing and handling methods that reflect their ecology, life history, and group-living characteristics. Here we introduce major principles and ethological considerations of colony management and husbandry. We provide clear instructions on laboratory practices necessary for maintaining a healthy and robust colony of degus for Alzheimer’s disease neuroscience research towards conducting reproducible studies. We also report detailed procedures and methodical information for degu Apoe genotyping and ethologically relevant burrowing behavioral tasks in laboratory settings.